Parasitos metazoários do Pseudoplatystoma corruscans (Spix & Agassiz, 1829) (Siluriformes: Pimelodidae) em sistema aquático tropical : aspectos ecológicos e patológicos. - Ribeiro, Thamy Santos (2013)
Effective management of our natural resources requires an understanding of ecosystem structure and function, by using an ecosystem-based approach to management. Despite the fact that parasites occur, albeit cryptically, in almost all ecosystems, yet they are usually neglected in studies on populations and communities of organisms. With the objective of evaluate the parasite community influence on the host population, and to observe the antropic alterations impact on the parasite fauna, 119 specimens of Pseudoplatystoma corruscans, popular known as "pintado" were collected. The specimens, obtained between March 2011 and September 2012, on the high Paraná river floodplain, has been processed according to the appropriated methodology to the acquirement of the metazoan parasites and to the performance of the histopathological analysis. Presents statistical comparison between the parasite fauna of before and after the construction of the Porto Primavera dam, demonstrating how the parasite community responds to the environmental alterations. Demonstrates, through histopathological analyses the host`s answer to a more aggressive infection of the Nomimoscolex pertierrae cestode. It evidenciates that the parasites are effective indicators of many aspects of the host biology, besides their importance to the environmental conservancy.